Microarray-based Gene Expression Profiling of Abdominal Aortic Aneurysm. Issue 1 (July 2016) - Butt, H.Z.; Sylvius, N.; Salem, M.K.; Wild, J.B.; Dattani, N.; Sayers, R.D.; Bown, M.J.
Abstract : Objective/Background: Microarray-based gene expression profiling studies may detect transcriptional signatures carrying prognostic value in abdominal aortic aneurysms (AAA). A gene expression profiling study was conducted to compare individuals with AAA with screened controls. Methods: The peripheral blood transcriptome was compared between 12 individuals with AAA and 12 age- and sex-matched controls using microarray. Validation by Taqman real-time quantitative (qPCR) was performed in an independent group as described. Peripheral blood RNA was hybridized to Illumina microarrays, each representing 37, 846 genes, allowing comparison of gene expression between cases and controls. Eleven differentially expressed genes were re-quantified by qPCR in the independent group with AAA ( n = 95), controls ( n = 92), pre- and postendovascular AAA repair (EVAR, n = 31); or open AAA repair ( n = 13), AAA wall biopsies ( n = 11), and in matched smooth muscle cultures ( n = 7). Results: Microarray detected 47 significantly differentially expressed genes in AAA after correction for multiple testing ( p < .05). These genes conferred roles in regulation of apoptosis, proteolysis, the electron transport chain, leukocyte migration, and the humoral immune response. Gene quantification in the independent group demonstrated three genes to be downregulated in AAA compared with controls: MSN, PSMB10, and STIM1 ; however, their expression remained unchanged post-AAA repair. PSMB10 was the only gene conferring a consistent direction of effect in both the discovery and validation analyses (downregulated). EIF3G, SIVA, PUF60, CYC1, FIBP, and CARD8 were downregulated post-EVAR. Expression of all 11 genes of interest was detected in aortic biopsies and matched smooth muscle cultures. Conclusion: This study demonstrates differential expression of transcripts in peripheral blood of individuals with AAA, with functional roles in proteolysis, inflammation, and apoptotic processes. These were modulated by aneurysm exclusion from the circulation and expressed in matched aortic biopsies and smooth muscle cultures. These observations further support the key roles for these pathways in the pathogenesis of AAA.